Resolusi Degradasi Pendidikan Desa Banyusidi melalui Program “Bhumi Literasi” Berbasis Digital - Wastiana; Siti Imronah; Winasti Rahma Diani (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2024)
Purpose – The aim of the “Bhumi Literacy” program is to overcome the decline in education in Banyusidi Village and reinvigorate the literacy spirit of the target participants. Methodology – One of the crucial problems is the degradation of education as evidenced by the high school dropout rate and the decline in literacy. To overcome this, the Ormawa Student Association of the Indonesian Language and Literature Education Study Program through the Student Organization Capacity Strengthening Program (PPK Ormawa) carries out community empowerment activities with the "Bhumi Literacy" program. Bhumi Literasi is a program for cultivating and developing children's literacy skills through non-formal education activities. The Bhumi Literacy Program is implemented using preparation, implementation, monitoring and evaluation methods, as well as hearings and partner assistance. Findings – Through this method, five literacy sub-programs were developed which will be implemented, namely sub-programs for scientific literacy, digital literacy, financial literacy, reading-writing literacy and cultural literacy. The five sub-programs produce outputs in the form of local cultural wisdom products in the form of succulent plants, pine hangers, pine bouquets, mugs and tote bags created by the trained participants. Originality – Apart from producing concrete and useful outcomes, the "Bhumi Literacy" program is a service program designed within the non-formal education curriculum to adapt to the educational needs of children in the digital era. The learning process that takes place is very innovative, fun and meaningful.